2020
DOI: 10.1186/s12957-020-01973-x
|View full text |Cite
|
Sign up to set email alerts
|

Multivisceral resection for adenocarcinoma of the pancreatic body and tail—a retrospective single-center analysis

Abstract: Background Adenocarcinoma of the pancreatic body and tail is associated with a dismal prognosis. As patients frequently present themselves with locally advanced tumors, extended surgery including multivisceral resection is often necessary in order to achieve tumor-free resection margins. The aim of this study was to identify prognostic factors for postoperative morbidity and mortality and to evaluate the influence of multivisceral resections on patient outcome. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
1
11
0
1
Order By: Relevance
“… 22 Additionally, relatively high rates of postoperative complications of extended surgery also prevented the treatment of surgery to some degree. 26 Considering the fact that progression of local disease, other than distant metastasis, contributed to most of the mortalities of LAPC patients, local destructive method is worthy of being tried. 27 As a non-thermal local destructive method, IRE induces apoptosis of tumor cells through causing irreversible permeabilization in cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 Additionally, relatively high rates of postoperative complications of extended surgery also prevented the treatment of surgery to some degree. 26 Considering the fact that progression of local disease, other than distant metastasis, contributed to most of the mortalities of LAPC patients, local destructive method is worthy of being tried. 27 As a non-thermal local destructive method, IRE induces apoptosis of tumor cells through causing irreversible permeabilization in cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…22 Additionally, relatively high rates of postoperative complications of extended surgery also prevented the treatment of surgery to some degree. 26 Considering the fact that progression of local disease, other than distant metastasis, contributed to most of the…”
Section: Discussionmentioning
confidence: 99%
“…In terms of relative risk, the above-mentioned authors [ 23 ] report an almost 6-fold increase in the risk of complications with concurrent colectomy in their univariate analysis, but not in their multivariable analysis. Beetz et al [ 26 ] showed that clinically-relevant pancreatic fistula was more frequent after extended distal pancreatectomy, but without statistical significance. Hartwig et al [ 8 ] found that extended DP was associated with a significant increase in overall and surgical morbidity but not mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Extended surgery including vascular resection is often necessary in order to achieve tumor-free resection margins. A relatively high postoperative complications of extended surgery compared with standard pancreatectomy would also decrease survival to some degrees ( 14 ). Considering the tumor biology and the response to neoadjuvant chemotherapy, usually surgical resection was performed in patients whose CA19-9 levels decreased by more than a half after neoadjuvant chemotherapy ( 10 ).…”
Section: Discussionmentioning
confidence: 99%